Bering Strait: a linguistic area bridging two continents - Kaplan, Lawrence D. (Journal de la société des américanistes, 2019)
Michèle Therrien’s work has taken a wide view of Inuit culture, includes the physical world, and looks at relationships with the spiritual world along with the Inuit universe in general, through language and metaphor. Works like Le corps inuit talk about wider relationships of vocabulary with different parts of the Inuit world, including the kayak, other conveyances, and the snow house, for example. For Therrien the Inuit world is a broad system composed of elements linked to one another, clo.